Development and Validation of the Career Identity Development Inventory. (November 2022) - Wendling, Elodie; Sagas, Michael
The primary aims of this study were to address existing measurement concerns in the neo-Eriksonian identity literature and fill a gap in the vocational identity literature by developing and validating the Career Identity Development Inventory (CIDI). As the processes of identity formation and career development share close conceptual ties, we introduced an integrated conceptual model of career identity development from which CIDI was developed to be comprised of two subscales, CIDI-E and CIDI-C, that were each composed of four career identity dimensions. In Study 1, we delineated how CIDI was constructed and reported initial evidence of validity and reliability using a sample of 398 US college graduates. We further tested the psychometric properties of CIDI in Study 2 using confirmatory factor analyses with another sample of 419 US college graduates. Implications for using CIDI at the variable and person level, and future research directions are provided to further the understanding of the career identity development process.